2021
DOI: 10.1101/2021.11.11.468190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoupling the molecular regulation of perenniality and flowering in bulbous barley (Hordeum bulbosum)

Abstract: Global crop production is being challenged by rapid population growth, declining natural resources, and dramatic climatic turnovers. These challenges have prompted plant breeders to explore new ventures to enhance adaptation and sustainability in crops. One intriguing approach to make agriculture more sustainable is by turning annual systems into perennial which offers many economic and biodiversity-friendly benefits. Previous attempts to develop a perennial cereal crop employed a classical breeding approach a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Bulbous barley has also been proposed as a target for de novo domestication 50 . With genome sequences in hand and enough knowledge about domestication genes in barley 51 , it should to edit their homologs in crop wild relatives so as to abolish seed shattering, adapt owering times to farmers' needs and increase seed set 50,52,53 . Still, the new domesticates might not contribute as much to human sustenance as hoped for 54 , but they would be valuable tools for plant scientists and evolutionary geneticists.…”
Section: Discussionmentioning
confidence: 99%
“…Bulbous barley has also been proposed as a target for de novo domestication 50 . With genome sequences in hand and enough knowledge about domestication genes in barley 51 , it should to edit their homologs in crop wild relatives so as to abolish seed shattering, adapt owering times to farmers' needs and increase seed set 50,52,53 . Still, the new domesticates might not contribute as much to human sustenance as hoped for 54 , but they would be valuable tools for plant scientists and evolutionary geneticists.…”
Section: Discussionmentioning
confidence: 99%
“…In barley, genome sequencing of perennial H. bulbosum and annual H. vulgare is facilitating such research. As an alternative to the creation of interspecific annual-perennial crosses, presence and absence variant (PAV) analysis has been conducted between the two species to identify genetic differences (Fuerst et al, 2021). Within the H. bulbosum genome, Fuerst et al (2021) identified a significant enrichment of developmental and disease resistance genes absent among annual Poaceae species, alongside those associated with bulb formation relating to starch biosynthesis.…”
Section: Elucidating the Genetic And Physiological Basis Of Perennialismmentioning
confidence: 99%
“…As an alternative to the creation of interspecific annual-perennial crosses, presence and absence variant (PAV) analysis has been conducted between the two species to identify genetic differences (Fuerst et al, 2021). Within the H. bulbosum genome, Fuerst et al (2021) identified a significant enrichment of developmental and disease resistance genes absent among annual Poaceae species, alongside those associated with bulb formation relating to starch biosynthesis. These findings, and further interrogation of this PAV dataset, should help identify the genes and processes responsible for perennial-to-annual conversion, making them available for reverse engineering.…”
Section: Elucidating the Genetic And Physiological Basis Of Perennialismmentioning
confidence: 99%
See 1 more Smart Citation